A systematic overview of fossil osmundalean ferns in China: Diversity variation, distribution pattern, and evolutionary implications - Tian, Ning; Wang, Yong-Dong (王永栋); Dong, Man; Li, Li-Qin (李丽琴); Jiang, Zi-Kun (Palaeoworld, 2016)
The order Osmundales is a unique fern taxon with extensive fossil records in geological past. Diverse osmundalean fossils have been reported from China, ranging in age from the Late Palaeozoic to the Cenozoic. Most of them are based on leaf impressions/compressions, but permineralized rhizomes are also well documented. In this study, we provide a systematic overview on fossil osmundalean ferns in China with special references on diversity variations, distribution patterns, and evolutionary implications. Fossil evidence indicates that this fern lineage first appeared in the Late Palaeozoic in China. The Late Triassic to Middle Jurassic interval was the radiation stage. From the Late Jurassic onward, fossil diversity declined rapidly. Cenozoic osmundalean taxa are represented by the relict species of Osmunda. Geographically, osmundalean fossils are found from both the Northern and Southern phytoprovinces of China, though variations are documented for geographical ranges. The Chinese fossil records cover almost all important stages for the macroevolution of the Osmundales, and contribute to further understanding of evolutionary processes of this peculiar fern lineage. (C) 2015 Elsevier B.V. and Nanjing Institute of Geology and Palaeontology, CAS. All rights reserved.